Examining the Intersection of Race, Ethnicity, Culture, Language, and Severe Disability: In Search of Equitable Schooling. (September 2022) - Dukes, Charles; Darling, Sharon M.; Rivera, Christopher J.
In this special section of Research and Practice for Persons with Severe Disabilities ( RPSD ), the intersection of race, ethnicity, culture, and language influences schooling (i.e., what is taught, how, and where) for students of color with significant cognitive disabilities is explored. Contemporary issues facing people of color with severe disabilities are introduced with attention paid to a call for a "way forward."